2021
DOI: 10.1093/mnrasl/slab014
|View full text |Cite
|
Sign up to set email alerts
|

Phase curve and variability analysis of WASP-12b using TESS photometry

Abstract: We analyse Sector 20 TESS photometry of the ultra-hot Jupiter WASP-12b, and extract its phase curve to study the planet’s atmospheric properties. We successfully recover the phase curve with an amplitude of 549 ± 62 ppm, and a secondary eclipse depth of 609$^{+74}_{-73}$ ppm. The peak of the phase curve is shifted by 0.049 ± 0.015 in phase, implying that the brightest spot in the atmosphere is shifted from the substellar point towards the planet’s evening terminator. Assuming zero albedo, the eclipse depth inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Although numerous phase curves of hot Jupiters have also exhibited signals associated with Doppler boosting and tidal ellipsoidal distortion (e.g. Shporer et al 2014;Wong et al 2020b;Owens et al 2021), relations presented by Morris (1985), Morris & Naftilan (1993), and Shporer et al (2019) suggest that the amplitude of these signals for MASCARA-1 would be roughly 10 ppm and 25 ppm, respectively. As we would be unable to significantly detect signals of these size in the Spitzer phase curve and due to the limited phase coverage of the CHEOPS data, we did not fit for these signals in our model.…”
Section: Planetary Modelmentioning
confidence: 99%
“…Although numerous phase curves of hot Jupiters have also exhibited signals associated with Doppler boosting and tidal ellipsoidal distortion (e.g. Shporer et al 2014;Wong et al 2020b;Owens et al 2021), relations presented by Morris (1985), Morris & Naftilan (1993), and Shporer et al (2019) suggest that the amplitude of these signals for MASCARA-1 would be roughly 10 ppm and 25 ppm, respectively. As we would be unable to significantly detect signals of these size in the Spitzer phase curve and due to the limited phase coverage of the CHEOPS data, we did not fit for these signals in our model.…”
Section: Planetary Modelmentioning
confidence: 99%
“…Turner et al (2021) analyzed the transits and secondary eclipses and used the measured timings to calculate a refined orbital decay rate for WASP-12b. The full-orbit phase curve of the WASP-12 system was analyzed independently by Owens et al (2021) in a standalone paper and by Wong et al (2021a) as part of a systematic phase-curve study of short-period exoplanet systems observed during the second year of the TESS mission.…”
Section: Observations 21 Tess Light Curvesmentioning
confidence: 99%
“…The light curves provided additional transit timings, which were used to refine the estimate of the planet's orbital decay rate (Turner et al 2021). Meanwhile, the planetary phase curve was analyzed by Owens et al (2021) and Wong et al (2021a), yielding a robust secondary eclipse measurement and broad constraints on the day-night temperature contrast. No evidence for significant orbit-toorbit variability in the dayside brightness was found in the TESS photometry.…”
mentioning
confidence: 99%
“…Maciejewski et al (2016) were the first to detect its decreasing orbital period, and subsequent studies have confirmed the period change (Patra et al 2017;Maciejewski et al 2018;Bailey & Goodman 2019;Baluev et al 2019) and established orbital decay as its cause (Yee et al 2020). The decaying orbit of WASP-12b was confirmed also using transit and occultation observations with NASA's Transiting Exoplanet Survey Satellite (TESS; Ricker et al 2015) (Turner et al 2021, see also Owens et al 2021). The decay rate of WASP-12b was found to be 32.53±1.62 msec yr −1 corresponding to an orbital decay timescale of τ = P/| Ṗ | = 2.90 ± 0.14 Myr (Turner et al 2021), shorter than the estimated mass-loss timescale of 300 Myr (Lai et al 2010;Jackson et al 2017).…”
Section: Introductionmentioning
confidence: 87%